2020
DOI: 10.1093/ckj/sfaa151
|View full text |Cite
|
Sign up to set email alerts
|

Impact of electronic alerts for acute kidney injury on patient outcomes: interrupted time-series analysis of population cohort data

Abstract: Background Automated acute kidney injury (AKI) electronic alerts (e-alerts) are rule-based warnings triggered by changes in creatinine and are intended to facilitate earlier detection in AKI. We assessed the impact of the introduction in the Tayside region of UK in April 2015 of automated AKI e-alerts with an accompanying education programme. Methods Interrupted time-series analysis using segmented regression was performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…However, the time series study design did not allow changes due to the alerting system to be differentiated those that happened independently. In a similarly designed study from Scotland, the introduction of automated AKI alerts was not associated with change in AKI incidence or severity, nor on mortality, although there was a small reduction in hospital length of stay [28]. This reduction in hospital length of stay has been reported in previous studies [29], including in the multicentre cluster randomized Tackling AKI study in which an AKI alerting system was evaluated as part of a more complex intervention [30].…”
Section: Acute Kidney Injury Detection and Alertingsupporting
confidence: 65%
“…However, the time series study design did not allow changes due to the alerting system to be differentiated those that happened independently. In a similarly designed study from Scotland, the introduction of automated AKI alerts was not associated with change in AKI incidence or severity, nor on mortality, although there was a small reduction in hospital length of stay [28]. This reduction in hospital length of stay has been reported in previous studies [29], including in the multicentre cluster randomized Tackling AKI study in which an AKI alerting system was evaluated as part of a more complex intervention [30].…”
Section: Acute Kidney Injury Detection and Alertingsupporting
confidence: 65%
“…Nonetheless, there exist some drawbacks. In an observational cohort study with segmented regression analysis conducted in U.K., the implementation of electronic AKI alert system and AKI-related staff education did not show a reduction in the severity and mortality associated with AKI [12]. In a previous study conducted in Korea, while the implementation of electronic AKI alerts with automated nephrologist consultation improved the likelihood of AKI recovery, the mortality of AKI patients was not affected [13].…”
Section: Introductionmentioning
confidence: 82%
“…However, 10 nonrandomized clinical trials and 3 randomized clinical trials (RCTs) of the alert system had mixed results. Seven of 10 nonrandomized clinical trials reported improved patient-centered outcomes, including improved AKI recovery, reduced mortality and dialysis rates, and decreased hospital length of stay (LOS) . In contrast, RCT results have suggested that AKI alerts were less beneficial, possibly even causing harm in specific instances .…”
Section: Introductionmentioning
confidence: 99%
“…Seven of 10 nonrandomized clinical trials reported improved patient-centered outcomes, including improved AKI recovery, 5 , 6 , 7 reduced mortality and dialysis rates, 8 , 9 , 10 and decreased hospital length of stay (LOS). 9 , 11 , 12 In contrast, RCT results have suggested that AKI alerts were less beneficial, possibly even causing harm in specific instances. 13 , 14 , 15 A 2015 trial by Wilson et al 13 showed increased dialysis rates in the surgical ward subgroup.…”
Section: Introductionmentioning
confidence: 99%